Profound Love and Dialogue: Paulo Freire and Liberation Education - Darriel B. Harris; Debra L. Roter (SLACK Incorporated, 2024)
Paulo Freire, Brazilian philosopher and educator, proposed an educational method for adults based on what he called "the problem posing method." This method was based on dialogue that he deemed necessary for education and was not oppressive and controlling. Freire argued that traditional educational methods were inherently oppressive because they served the interest of the elite, instituted what he called "the banking method" in hopes to turn people into better workers. In contrast to this, Freire advocated for an education that was liberating and required dialogue. Dialogue, however, could only take place with profound love. This article reflects on Freire's call for profound love and dialogue within his pedagogical framework, and its necessity for social and political change. Further, this article explores what Freire meant by profound love and dialogue, and explores how love and dialogue are applicable to current and future health literacy and health education efforts. [HLRP: Health Literacy Research and Practice. 2024;8(3):e118-e120.]